Supercritical Extraction Process of Allspice Essential Oil - Yasvet Y. Andrade-Avila; Julian Cruz-Olivares; César Pérez-Alonso; Ciro Humberto Ortiz-Estrada; María del Carmen Chaparro-Mercado (Journal of Chemistry)
Allspice essential oil was extracted with supercritical carbon dioxide (SC-CO2) in a static process at three different temperatures (308.15, 313.15, and 318.15 K) and four levels of pressure (100, 200, 300, and 360 bar). The amount of oil extracted was measured at intervals of 1, 2, 3, 4, 5, and 6 h; the most extraction yield reached was of 68.47% at 318.15 K, 360 bar, and 6 h of contact time. In this supercritical extraction process, the distribution coefficient (KD), the mean effective diffusion coefficient (Def), the energy of activation (Ea), the thermodynamic properties (ΔG0, ΔH0, and ΔS0), and the apparent solubility (S) expressed as mass fraction (w/w) were evaluated for the first time. At the equilibrium the experimental apparent solubility data were successfully correlated with the modified Chrastil equation.